2013
DOI: 10.5194/nhess-13-2189-2013
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: On the relation between the seismic activity and the Hurst exponent of the geomagnetic field at the time of the 2000 Izu swarm

Abstract: Many papers document the observation of earthquake-related precursory signatures in geomagnetic field data. However, the significance of these findings is ambiguous because the authors did not adequately take into account that these signals could have been generated by other sources, and the seismogenic origin of these signals have not been validated by comparison with independent datasets. Thus, they are not reliable examples of magnetic disturbances induced by the seismic activity. Hayakawa et al. (2004) cla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The most commonly used methods to identify preearthquake ULF anomalies in geomagnetic field records are the so called spectral polarization ratio analysis [see, e.g., Hayakawa et al ., ] and fractal analysis [ Hayakawa et al ., ]. Fractal anomalies preceding earthquakes have been extensively discussed and denied as precursors by Masci [, ] and Masci and Thomas [, , ]. Reports of precursory signatures in the spectral polarization ratio were proved invalid as well [see, e.g., Masci , , , ; Masci and Thomas , ; Thomas et al ., ].…”
Section: Are Magnetic Polarization Ratio Anomalies Credible Precursormentioning
confidence: 99%
See 3 more Smart Citations
“…The most commonly used methods to identify preearthquake ULF anomalies in geomagnetic field records are the so called spectral polarization ratio analysis [see, e.g., Hayakawa et al ., ] and fractal analysis [ Hayakawa et al ., ]. Fractal anomalies preceding earthquakes have been extensively discussed and denied as precursors by Masci [, ] and Masci and Thomas [, , ]. Reports of precursory signatures in the spectral polarization ratio were proved invalid as well [see, e.g., Masci , , , ; Masci and Thomas , ; Thomas et al ., ].…”
Section: Are Magnetic Polarization Ratio Anomalies Credible Precursormentioning
confidence: 99%
“…What is more important, this correspondence is not expected always and everywhere. Conversely, if it is shown that there is close correspondence between alleged ULF magnetic precursors and geomagnetic indices (e.g., Kp ) [see Masci , , , , , , ; Masci and Thomas , , ], this indicates that the magnetic changes are part of global geomagnetic field changes and cannot be described as earthquake‐related signals. Therefore, the real issue is not the poor correlation that Currie and Waters [] have found between local ULF magnetic changes and geomagnetic indices but the correspondence that many papers have shown between ULF magnetic changes claimed to be precursors of earthquakes and global geomagnetic activity changes.…”
Section: The Study By Currie and Waters []mentioning
confidence: 99%
See 2 more Smart Citations
“…Hurst exponent ( H ) is estimated by the slope of the best fit line in log ( R n / S n ) versus log ( n ) representation of the R n / S n power law [see Masci and Thomas , ].…”
Section: Resultsmentioning
confidence: 99%